DESAIN AUTOMATIC CONTROL SYSTEM POMPA AIR TAWAR PADA KAPAL RAKYAT - Franky Tanahitumessing (Fakultas Teknik Universitas Pattimura, 2021)
Freshwater supplies on people's ships are a vital need that must be met during the ship's voyage. The distribution system used without control will be troublesome for the Crew, who are always in charge of controlling the availability of water in the daily tank and running the water pump. Water pump control equipment is used to help reduce the working time of the Crew and can improve the performance efficiency of the water pump. A buoy switch is a control tool that is often used, but the buoy system will be disrupted over time. An automatic control system using a water level sensor is not familiar to use to control the water pump. From the design results of this system is more efficient than the buoy switch. Its efficiency can be seen from the degree of sensitivity to changes in water level, as well as longer service life. This system can be used to control the work of water pumps without supervision or control of the Crew, thus saving more time and the availability of water in the daily tank remains available at all times.